Effectiveness of the Prolanis Program in Controlling Blood Pressure among Hypertension Patients at Doktor Fuzti Clinic - Fauzia, Fuzti; Hamdani, Dadi (Genius Journal, 2025)
Introduction: Chronic health conditions caused by genetic, physiological, and environmental factors are common among individuals with Non-Communicable Diseases (NCDs). Hypertension is one of the most prevalent chronic NCDs. If left untreated, it may lead to serious complications such as heart disease, stroke, and kidney failure. Effective management strategies are crucial to control blood pressure and prevent further health risks. Objective: This study aimed to evaluate the effectiveness of the Chronic Disease Management Program (Prolanis) as a healthcare initiative to control blood pressure in patients with hypertension. Methods: A quantitative one-group pre-test and post-test design was employed. A total of 25 participants diagnosed with hypertension were selected using purposive sampling based on predefined inclusion criteria. Blood pressure was measured before and after participation in the Prolanis program. The data were analyzed using the paired sample t-test. Results: The analysis showed a statistically significant reduction in mean systolic blood pressure from 154 mmHg to 136 mmHg after the intervention. The paired sample t-test yielded a p-value of 0.001 (p < 0.05), indicating that the observed reduction was significant. Conclusion: The findings suggest that the Prolanis program is effective in controlling blood pressure among hypertensive patients. Integrating structured chronic disease management programs like Prolanis into routine healthcare services can contribute to improved patient outcomes and reduced risk of complications associated with hypertension.